DIAGNOSTICS OF AIRCRAFT GASTURBINE ENGINES BY THE PRESENCE OF HARMFUL IMPURITIES IN THE AIR CONDITIONING SYSTEM - O. F. Mashoshin; G. S. Zontov (Научный вестник МГТУ ГА)
The article considers the control of the state of aviation gas turbine engine (GTE), based on the analysis of harmful substances impurities in the air conditioning system in order to predict seal wear of rotor supports, the state of which largely affects the performance and efficiency of gas turbine engines, without removing it from the aircraft.